PENGUKURAN KETERAMPILAN LITERASI DIGITAL DI KALANGAN MAHASISWA FIKOM UNIVERSITAS PROF. DR. MOESTOPO (BERAGAMA) - Handayani, Mediana (Universitas Prof. Dr. Moestopo (Beragama), 2018)
This study examined digital media literacy skills of university students based on Jenkins and his colleagues’ classification. Toward this purpose, an Likert scale was administered to a sample (n=150). This scale included a multi-component understanding of media literacy such as tackling the consumption of media messages and the original creation of multimedia material. This study also aimed to assess participants’ new media literacy skills by presenting about their social and cultural modes of engagement, online interaction, and media consumption and creation patterns. The statements were conceptually built around the 12 new media literacy levels skills identified by Jenkins and his colleagues. These skills are: Play, appropriation, distributed cognition, collective intelligence, judgment, transmedia navigation, networking, negotiation, and visualization. The results of the study showed that individuals who spent more time on Internet, social media, and blogging had the highest media literacy skills levels. Furthermore, the average of new media literacy levels among respondents were quite good and well, and there is no significant difference in the new media literacy skills based on the demographics of respondents.